Did employer sanctions lose their bite? Labor market effects of immigrant legalization - Magnus Lofstrom; Laura Hill; Joseph Hayes (Institute for the Study of Labor (IZA), 2010)
Taking advantage of the ability to identify immigrants who were unauthorized to work prior to obtaining Legal Permanent Resident status, we use the New Immigrant Survey to examine whether lacking legal status to work in the U.S. constrains employment outcomes of illegal immigrants. With the exception of high-skilled unauthorized immigrants, the data fail to reveal evidence of improved employment outcomes attributable to legal status. In light of evidence that unauthorized immigrants experienced increased wages as a result of receiving amnesty through the 1986 Immigration and Reform Control Act during the 1990s, we interpret the results as evidence of ineffective employer sanctions.
Keywords: J8; J15; J18; J31; J61; 330; Unauthorized; illegal; undocumented; immigration; legalization; amnesty; Migranten; Illegale Einwanderung; Ausländische Arbeitskräfte; Lohndifferenzierung; Legalisierung; Wirkungsanalyse; Berufliche Integration; USA